Role of G-proteins in the effects of leptin on pedunculopontine nucleus neurons - Beck, Paige (2013)
The pedunculopontine nucleus (PPN), the cholinergic arm of the reticular activating system, regulates waking and rapid eye movement sleep. Here, we demonstrate immunohistochemical labeling of the leptin receptor signaling isoform in PPN neurons, and investigated the effects of G-protein modulation and the leptin triple antagonist (TA) on the action of leptin in the PPN. Whole-cell patch clamp recordings were performed in rat brainstem slices from 9 to 17 day old pups. Previous results showed that leptin caused a partial blockade of sodium (INa) and h-current (IH) in PPN neurons. TA (100 nM) reduced the blockade of INa (~ 50% reduction) and IH (~ 93% reduction) caused by leptin. Intracellular guanosine 5′-[b-thio] diphosphate trilithium salt (a G-protein inhibitor) significantly reduced the effect of leptin on INa(~ 60% reduction) but not on IH (~ 25% reduction). Intracellular GTPcS (a G-protein activator) reduced the effect of leptin on both INa (~ 80% reduction) and IH (~ 90% reduction). These results suggest that the effects of leptin on the intrinsic properties of PPN neurons are leptin receptor- and G-protein dependent. We also found that leptin enhanced NMDA receptor-mediated responses in single neurons and in the PPN population as a whole, an effect blocked by TA. These experiments further strengthen the association between leptin dysregulation and sleep disturbances.